Pneumatic As A Future Or Alternative Energy Storage System - Khalid, Muhammad Syazwan Abdul (Universiti Sains Malaysia, 2021)
ix Abstract Pneumatic energy storage system is a system that benefits compressed air as the input to produce desirable output such as mechanical energy and electrical energy. There are several of CAES plants in USA and Germany, but Malaysia is not quite familiar with it. Through this project, a simple and small-scale compressed air storage energy system will be built by using old and reusable things as a part of the system. The system will be focusing on the rural areas which means that any complex mechanism or scientific law are not recommended. Initially, a wind turbine is suggested to provide the input, but it is replaced with an electrical car air pump because of some obstacles during the pandemic. There are several designs have been issued for the project and the design concepts are sketched out to provide a clear picture of each design. One of the designs will be chosen according to the pros and cons of the design. After the fabrication of the system done, the system will proceed to the experiment to collect data needed. The results are obtained, analyzed and the conclusion has been made. The efficiency of the system is very low due to some restrictions and weaknesses of the system which is the turbine is not secured with a closed region, the low efficiency of the turbine and the presence of micro-leaks on the air tank which lead to high power loss.